2019
DOI: 10.14701/ahbps.2019.23.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes in elective laparoscopic cholecystectomy

Abstract: Backgrounds/Aims Traditional outcome measures (e.g., length of hospital stay, morbidity, and mortality) are used to determine the quality of care, but these may not be most important to patients. It is unclear which outcomes matter to patients undergoing elective laparoscopic cholecystectomy (ELC). We aim to identify patient-reported outcome measures (PROM) which patients undergoing ELC valued most. Methods A 45-item questionnaire with Four-point Likert-type questions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…We continued to prioritize patients with symptoms of groin pain or recurrent attacks of biliary colic to reduce the impact on quality of life and maintain good patient-reported outcomes [ 18 , 19 ]. The number of first outpatient visits to surgical clinics for new patients decreased by about one-half.…”
Section: Discussionmentioning
confidence: 99%
“…We continued to prioritize patients with symptoms of groin pain or recurrent attacks of biliary colic to reduce the impact on quality of life and maintain good patient-reported outcomes [ 18 , 19 ]. The number of first outpatient visits to surgical clinics for new patients decreased by about one-half.…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision-making is critical to ensure treatment decisions align with patients’ values and understanding the factors influencing patient decision-making is necessary in this process [ 19 ]. One prior study found that perceived autonomy and effective surgeon communication were as important as expected postoperative quality of life in patients’ decisions to undergo cholecystectomy [ 20 ]. In this cohort of US adults with gallbladder disease we show that after severity of symptoms, cost of surgery and time off from work were the most important factors in considering cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Mak et al reported the alignment of patient-reported outcomes to patient needs, physician views and policymaker decisions. 15 In this study, we conducted a patient survey on their experience and perception of early postoperative mobilisation before discharge. Fifty per cent (10 of 20) of the patients did not mobilise due to wound pain and 30% (6 of 20) due to multiple tubes connected to the body.…”
Section: Discussionmentioning
confidence: 99%